Targeting neuroinflammation reduces synaptic, neuronal and cognitive loss in 5xFAD Alzheimer mice. (20th December 2022) - Lecca, Daniela; Yung, Yoo Jin; Scerba, Michael T; Tweedie, David; Hsueh, Shih Chang; Hoffer, Barry; Kim, Dong Seok; McDevitt, Ross A; Greig, Nigel H
Abstract: Background: Neuroinflammation is a consistent characteristic of Alzheimer's disease (AD); however, whether its development drives disease progression or is an epiphenomenon remains unknown (Gyengesy et al., 2020). In this study, we evaluated how treatment with the Immunomodulatory imide drugs ( IMiDs ) Pomalidomide (Pom) and more potent novel analog 3, 6'‐dithioPomalidomide (3, 6'‐DP) affects neuronal and synaptic loss as well as cognitive impairment in a 5xFAD transgenic mouse model of AD, by targeting neuroinflammation. These mice are known to develop neuroinflammation consequent to excessive amyloid‐b (Ab) peptide generation. Method: As a first step, Pom and 3, 6'‐DP neuroprotective and anti‐inflammatory potential were characterized on primary cell cultures challenged with Ab. 5xFAD mice were evaluated over a 4‐month period, during which cognitive deficits develop. Behavioral tests were performed to establish whether selective resolution of neuroinflammation could mitigate cognitive impairment. Pom and 3, 6'‐DP effects were assessed on markers of neuronal death, microglial activation, astrogliosis, and expression of PSD‐95 post‐synaptic protein. Changes in levels of inflammatory cytokines and Ab in hippocampus and cortex 5xFAD mice were also measured. Lastly, the teratogenic potential of both compounds was appraised by a cereblon/BRD3 binding FRET assay. Result: Pom and 3, 6'‐DP reduced neuronal and neurite network loss, as well as microglial cell activation in primary cortical cultures challenged with Ab. In hippocampus and cerebral cortex of 5xFAD mice, 3, 6'‐DP, in particular, mitigated elevated expression of Iba1, TNF‐a and GFAP proteins, markers of microglial and astrocyte activation. This was accompanied by reductions in synaptic and neuronal cell loss as well as mitigation of behavioral impairment but, notably, no alteration in either Ab plaque or peptide generation. Both 3, 6'‐DP and Pom bound cereblon; however, 3, 6'‐DP did not lower Ikaros, Aiolos or SALL4, which are key downstream neo‐substrates involved in the anticancer and teratogenic actions of the IMiD drug class. Hence, 3, 6'‐DP could represent a potentially safer drug to lower TNF‐a levels. Conclusion: Mitigating neuroinflammation in the absence of actions on Ab generation to alleviate neurodegeneration and behavioral impairment indicates that neuroinflammation is a primary causative event in the Ab‐mediated pathological cascade leading to neuronal loss/cognitive impairment. Targeting neuroinflammatory mediators with IMiDs represent a promising AD therapeutic strategy.